Screening for Diguanylate Cyclase (DGC) Inhibitors Mitigating Bacterial Biofilm Formation - Cho, Kyu Hong; Tryon, R. Grant; Kim, Jeong-Ho (Frontiers in Chemistry, 2020)
The majority of bacteria in the natural environment organize themselves into communal biofilms. This biofilm formation benefits bacteria conferring resistance to harmful molecules (e.g., antibiotics, disinfectants, and host immune factors) and coordinating their gene expression through quorum sensing (QS). A primary signaling molecule promoting bacterial biofilm formation is the universal second messenger cyclic di-GMP. This dinucleotide predominantly controls the gene expression of motility, adhesins, and capsule production to coordinate biofilm formation. Cyclic di-GMP is synthesized by diguanylate cyclases (DGCs) that have a GGDEF domain and is degraded by phosphodiesterases (PDEs) containing either an EAL or an HD-GYP domain. Since high cellular c-di-GMP concentrations are correlated with promoting the ability of bacteria to form biofilms, numerous research endeavors to identify chemicals capable of inhibiting the c-di-GMP synthesis activity of DGCs have been performed in order to inhibit bacterial biofilm formation. This review describes currently identified chemical inhibitors that disturb the activity of DGCs and the methods of screening and assay for their discovery.